Pengaruh kerapatan briket campuran tempurung kelapa dan bonggol jagung terhadap kinerja kompor biomassa - Khusaini, Risky; Rahman, Jhonni (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
The potential of biomass energy in Indonesia that can be used as an energy source is 146.7 tons per year. One of the renewable energy and its abundance is biomass, namely by making briquettes using a biomass stove. the purpose of this study is to determine the effect of coconut shell and corn stalk briquette speed on biomass stove performance. This test uses of variety of briquette felts, namely 1, 3, and 5 kg. The results showed that the density at pressures of 1, 3, and 5 kg produced densities of 0.843 g/cm3, 0.905 g/cm3, and 1.032 g/cm3. The difference in density affects the performance of the best felt pressure biomass stove at a pressure of 5 kg.